Implementing digital marketing using artificial intelligence - Qasim, Dhia; Khalifeh, Amin (International Journal of Innovative Research and Scientific Studies, 2025)
This paper aims to discuss the application of AI in digital marketing, its role in enhancing decision-making, personalization, and campaign performance along the customer’s journey. This study employs a qualitative research approach to investigate the strategic application of AI in digital marketing, drawing on recent academic literature, industry reports, and case studies. Thematic coding was applied to identify key patterns and emerging themes such as predictive analytics, customer personalization, and performance optimization. The key applications are big data analytics, content personalization, omnichannel integration, automated content generation, and dynamic customer interaction. The evidence suggests that the strategic use of AI not only enhances customer satisfaction and conversion rates but also improves operating efficiency and fosters long-term brand loyalty. As digital ecosystems continue to evolve, AI emerges as a key driver of innovation and digital marketing competitiveness. The study leverages existing academic and practical knowledge to describe how AI equips organizations with the capacity to manage enormous datasets, automate marketing functions, and deliver hyper-personalized experiences.